Study on Pore Structure of Shale Reservoir by Low Temperature Nitrogen Adsorption Method. (21st June 2022) - Mi, Huaying; Guo, Yujie; Yu, Xiaogang
Abstract : Shale gas is one of the most actively explored unconventional sources of natural gas. There are several types of pores in the shale reservoir, and their structural characteristics are complex. Evaluating the characteristics of the shale pore structure is the basis for understanding the shale reservoir performance and the oil and gas migration mechanism. In this paper, the micro- and nanopores of shale samples from the Yanchang Formation, Hunan basin, are studied by applying the low-temperature nitrogen adsorption method. Several pore structure parameters such as the specific surface area, the pore volume, and the pore size distribution of the analyzed samples are calculated. The predominant characteristics of nanopores that influence hydrocarbon accumulation and control the development of pores are discussed. The results indicate that the shale reservoir rocks from the study area are mainly mesoporous with an average pore size distribution between 2 and 50 nm. A small number of micropores (less than 2 nm) and macropores (more than 50 nm) are also present in the pore network. The development of micropores and mesopores in the shale samples is associated with organic matter content, while the development of macropores is linked to clay minerals content. Total organic carbon (TOC) content is the key element to control the nanopore volume and the specific surface area of the reservoir rocks from the study area. At the same time, the organic matter-enriched pore network also provides extensive space for the accumulation of shale gas.